Synthesis and biological activities of some Mannich bases of 5-(2-furyl)-1,2,4-triazole-3-thiones - Cansiz, A; Servi, S; Koparir, M; Altintas, M; Digrak, M (Chem Soc Pakistan, 2001)
A number of Mannich bases of 5-(2-furyl) -1,2,4- triazole-3- thiones (I-X) were prepared. The structures of the compounds have been established by elemental analysis and spectral (IR; H-1-NMR) data. Some selected Mannich bases were screened for their in vitro antibacterial activity against sonic bacteria, emploging the disk-diffusion technique.